Inclusion of Pichia guilliermondii on different culture media, on in vitro fermentation of Cynodon nlemfuensis - Marrero, Yoandra; Sosa, Dailyn; Rodríguez, R.; García, Yaneysi (Cuban Journal of Agricultural Science, 2016)
The objective of this study was to evaluate the effect of inclusion of Pichia guilliermondii on different culture media on in vitro fermentation of Cynodon nlemfuensis. In vitro gas production technique was used, as well as a completely randomized design, with 6 x 7 factorial arrangement (six treatments per seven hours of fermentation). A strain of P. guilliermondii (Levica 27) was included on one of the treatments, which was cultured in malt extract broth and extract of yeast-peptone-glucose media. Two of the treatments included the supernatant of each medium after centrifugation, and another treatment suspended again cell pellet in a buffer medium. A control without yeast was also included. An amount of 1 g of Cynodon nlemfuensis was incubated as fibrous substrate. Gas production was measured at 2, 4, 8, 12, 16, 20 and 24 h. Results showed that Levica 27 strain, cultured in malt extract broth and extract of yeast-peptoneglucose media, stimulated C. nlemfuensis gas production in a higher proportion (P < 0.001) than when it was cultured in a malt extract broth medium, which demonstrated the influence of metabolites thatproduce yeasts and their stimulating effect. Key words: yeasts, rumen, additives